Enteroendocrine-derived glucagon-like peptide-2 controls intestinal amino acid transport - Jennifer Lee (Molecular Metabolism, 2017)
Objective: Glucagon-like peptide-2 (GLP-2) is co-secreted with GLP-1 from gut endocrine cells, and both peptides act as growth factors to expand the surface area of the mucosal epithelium. Notably, GLP-2 also enhances glucose and lipid transport in enterocytes; however, its actions on control of amino acid (AA) transport remain unclear. Here we examined the mechanisms linking gain and loss of GLP-2 receptor (GLP-2R) signaling to control of intestinal amino acid absorption in mice. Methods: Absorption, transport, and clearance of essential AAs, specifically lysine, were measured in vivo by Liquid Chromatography triple quadrupole Mass Spectrometry (LC-MS/MS) and ex vivo with Ussing chambers using intestinal preparations from Glp2r+/+ and Glp2r−/− mice. Immunoblotting determined jejunal levels of protein components of signaling pathways (PI3K-AKT, and mTORC1-pS6-p4E-BP1) following administration of GLP-2, protein gavage, and rapamycin to fasted Glp2r+/+ and Glp2r−/− mice. Expression of AA transporters from full thickness jejunum and 4F2hc from brush border membrane vesicles (BBMVs) was measured by real-time PCR and immunoblotting, respectively. Results: Acute administration of GLP-2 increased basal AA absorption in vivo and augmented basal lysine transport ex vivo. GLP-2-stimulated lysine transport was attenuated by co-incubation with wortmannin, rapamycin, or tetrodotoxin ex vivo. Phosphorylation of mTORC1 effector proteins S6 and 4E-BP1 was significantly increased in wild-type mice in response to GLP-2 alone, or when co-administered with protein gavage, and abolished following oral gavage of rapamycin. In contrast, activation of GLP-1R signaling did not enhance S6 phosphorylation. Disruption of GLP-2 action in Glp2r−/− mice reduced lysine transport ex vivo and attenuated the phosphorylation of S6 and 4E-BP1 in response to oral protein. Moreover, the expression of cationic AA transporter slc7a9 in response to refeeding, and the abundance of 4F2hc in BBMVs following protein gavage, was significantly attenuated in Glp2r−/− mice. Conclusions: These findings reveal an important role for GLP-2R signaling in the physiological and pharmacological control of enteral amino acid sensing and assimilation, defining an enteroendocrine cell-enterocyte axis for optimal energy absorption. Author Video: Author Video Watch what authors say about their articles Keywords: GLP-2, GLP-1, Amino acid absorption, Rapamycin, Gut peptides